A Study on Women-Issues in the Novels of Shashi Deshpandey: Exploring the Plight of Women in Shashi Deshpande's Novels (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The current article endeavors to investigate the multifaceted idea of conjugal connections in Deshpande's tale, Strangers to Ourselves. Shashi Deshpande, the writer of ten books, two novellas, four books for kids and an enormous number of short stories, has been expounding on issues and issues of white collar class Indian ladies trapped in the snare of Indian male controlled society. She has a far reaching comprehension of the grass-root reality and ladies' place and position, distresses and sufferings, situation and issue, torment and misery in a male-driven Indian culture.Her ladies heroes, all around, wind up to be the casualties of uncalled for customs, shows and conventions which are supportive of men.Unfit to hold up under limitations and impulses forced on them for the sake of sexual orientation segregation in their parental homes, they use marriage as a getaway course, yet shockingly, by and large, marriage turns into a snare for them. They are embarrassed, tormented and misused in one way or the other. They face physical viciousness as undesirable conjugal sex, right around an assault and mental torment. Her books move around conjugal connections which are defaced by the shades of malice, for example, male pride, personality and control, man centric mentality to ladies, absence of comprehension and correspondence.